2009
DOI: 10.1097/ede.0b013e31819d9501
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Carbon Exposure at Residence and Survival After Acute Myocardial Infarction

Abstract: Chronic traffic-related particulate air pollution is associated with increased mortality in hospital survivors of acute MI after the second year of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…The results of a recent cohort study in California suggest that long-term exposure to OC also increase cardiopulmonary mortality (Ostro et al 2010). Additionally, several previous studies support the biological plausibility of a link between exposure to OC or EC and exacerbations of cardiopulmonary diseases (Gold et al 2005; Henneberger et al 2005; Jansen et al 2005; Lanki et al 2006; Lewne et al 2007; Mar et al 2005; Shih et al 2008; von Klot et al 2009). For example, one study in Germany examined weekly electrocardiograms of 56 men with a history of heart disease and found significant associations of OC or EC with changes in myocardial repolarization, which could increase the risk of sudden cardiac death (Henneberger et al 2005).…”
Section: Discussionmentioning
confidence: 61%
“…The results of a recent cohort study in California suggest that long-term exposure to OC also increase cardiopulmonary mortality (Ostro et al 2010). Additionally, several previous studies support the biological plausibility of a link between exposure to OC or EC and exacerbations of cardiopulmonary diseases (Gold et al 2005; Henneberger et al 2005; Jansen et al 2005; Lanki et al 2006; Lewne et al 2007; Mar et al 2005; Shih et al 2008; von Klot et al 2009). For example, one study in Germany examined weekly electrocardiograms of 56 men with a history of heart disease and found significant associations of OC or EC with changes in myocardial repolarization, which could increase the risk of sudden cardiac death (Henneberger et al 2005).…”
Section: Discussionmentioning
confidence: 61%
“…A second study of 1,120 AMI survivors in central Israel reported a positive but statistically nonsignificant association of PM 2.5 with post-AMI mortality (HR 10 = 1.3, 95% CI = 0.8, 2.1) (Koton et al 2013). Similarly, two separate cohort studies in the United States linked increased all-cause deaths among AMI patients to PM 10 (Zanobetti and Schwartz 2007) and elemental carbon (a proxy for traffic particles) (von Klot et al 2009). In contrast, no association was found for NO 2 with post-AMI survival in an Italian cohort of AMI patients (Rosenlund et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Among a small set of studies that have assessed the influence of long-term exposure to air pollution on mortality after AMI, three studies reported increased all-cause mortality in association with exposure to PM 2.5 (particles ≤ 2.5 μm in diameter) (Tonne and Wilkinson 2013), PM 10 (Zanobetti and Schwartz 2007), and elemental carbon (C) (von Klot et al 2009). However, in two other studies, no compelling evidence was found for associations with PM 2.5 (Koton et al 2013) or nitrogen dioxide (NO 2 ) (Rosenlund et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este método foi utilizado para o cálculo das concentrações de hidrocarbonetos em um estudo da exposição à poluição do ar durante a gravidez e sua associação com o peso ao nascer 44 . Diversos outros estudos utilizaram este método [45][46][47][48][49] . Para o municí-pio de São Paulo seriam necessários estudos para determinação dos padrões de emissão em função do uso e ocupação do solo.…”
Section: Avaliação Da Exposição à Poluição Relacionada Ao Tráfegounclassified